Math virtual assistant

Calculators Topics Go Premium About Snapxam
ENGESP

Step-by-step Solution

Solve the inequality $\left(x+1\right)\left(x-3\right)\leq 0$

Go
1
2
3
4
5
6
7
8
9
0
x
y
(◻)
◻/◻
2

e
π
ln
log
lim
d/dx
Dx
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

Answer

$-1\leq x\leq 3$

Step-by-step explanation

Problem to solve:

$\left(x+1\right)\left(x-3\right)\le\:0$
1

Solve the product $\left(x+1\right)\left(x-3\right)$

$x^2-2x-3\leq 0$
2

To find the roots of a polynomial of the form $ax^2+bx+c$ we use the quadratic formula, where $a=1$, $b=-2$ and $c=-3$

$x =\frac{-b\pm\sqrt{b^2-4ac}}{2a}$

Unlock this step-by-step solution!

Answer

$-1\leq x\leq 3$
$\left(x+1\right)\left(x-3\right)\le\:0$

Main topic:

Inequalities

Time to solve it:

~ 0.37 seconds